Exercício físico na melhora da qualidade de vida do indivíduo com insônia - Carlos Alberto Da Silva; Walter Celso De Lima (Universidade Federal do Rio Grande do Sul, 2001)
Nowadays, the prevalence of sleep disturbances in our environment is high. Insomnia is a very frequent complaint in the physician's offices, because of its important and close connection with other diseases, such as depression, anxiety, stress, affection problems, among others. The sleep disturbances have been more and more studied, as its repercussions affect not only the subject himself but all who surround him, by alterating his vitality, humor, performance and sociability. The goal of this work is to clarify and to update some aspects of function and auxiliar treatment of this disturbance by means of physical exercise, mainly evidencing the improvement of the quality of life of people who have this disturbance. This way, it's conclusive that physical exercise nowadays, is, without any doubt, part of the treatment of this disturbance, mainly evidencing relaxation, the effective improvement of the people involved in any oriented regular practice and the physiologic adaptations occurred coping with physical exercise, in a supposed better quality of life.